Interpretations of the Term “Watershed Line” Used as Reference for Volar Plating - Bergsma, Minke; Doornberg, Job N.; Hendrickx, Laurent; Hayat, Batur; Kerkhoffs, Gino M.M.J.; Jhadav, Bhavin; Jaarsma, Ruurd L.; Bain, Gregory I. (Journal of Wrist Surgery, 2020)
Objective The objective of this systematic review is to provide an overview of all interpretations of the definition of the watershed line used in literature.Methods The Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines were followed for this review. A comprehensive search was performed for definitions of the watershed line given in literature. A total of 32 studies giving an explicit interpretation of the definition of the watershed line or anatomical reference for plate positioning in writing and/or imaging were included.Results In 32 studies, we found eight different landmarks used to refer to the watershed line or correct plate positioning. Five studies used two different soft tissue landmarks. Six different bony landmarks were described in 24 studies. These could further be subdivided into three anatomical interpretations, described in seven studies, in which the term “watershed line” is explained as a distinguishable anatomical line, and two surgical interpretations, described in 15 studies, which are purely reflecting the optimal location of the volar plate. One interpretation of the watershed line described in two studies combined both anatomical and surgical landmarks.Conclusion The (mis)interpretation of the definition of the term “watershed line” as described by Orbay is subject to the type of landmarks and purpose used: soft tissue or bony landmarks and an anatomical or a surgical purpose. A clear distinction can be made between interpretations using bony landmarks, as the true watershed line is defined and definitions using soft tissue landmarks, which might represent the reference points surgeons use in clinical practice.
Keywords: distal radius; watershed; volar plating; anatomy; systematic review